Household sanitation is associated with lower risk of bacterial and protozoal enteric infections, but not viral infections and diarrhoea, in a cohort study in a low‐income urban neighbourhood in Vellore, India. Issue 9 (17th July 2017) - Berendes, David; Leon, Juan; Kirby, Amy; Clennon, Julie; Raj, Suraja; Yakubu, Habib; Robb, Katharine; Kartikeyan, Arun; Hemavathy, Priya; Gunasekaran, Annai; Roy, Sheela; Ghale, Ben Chirag; et al.
Abstract: Objective: This study examined associations between household sanitation and enteric infection – including diarrhoeal‐specific outcomes – in children 0–2 years of age in a low‐income, dense urban neighbourhood. Methods: As part of the MAL‐ED study, 230 children in a low‐income, urban, Indian neighbourhood provided stool specimens at 14–17 scheduled time points and during diarrhoeal episodes in the first 2 years of life that were analysed for bacterial, parasitic (protozoa and helminths) and viral pathogens. From interviews with caregivers in 100 households, the relationship between the presence (and discharge) of household sanitation facilities and any, pathogen‐specific, and diarrhoea‐specific enteric infection was tested through mixed‐effects Poisson regression models. Results: Few study households (33%) reported having toilets, most of which (82%) discharged into open drains. Controlling for season and household socio‐economic status, the presence of a household toilet was associated with lower risks of enteric infection (RR: 0.91, 95% CI: 0.79–1.06), bacterial infection (RR: 0.87, 95% CI: 0.75–1.02) and protozoal infection (RR: 0.64, 95% CI: 0.39–1.04), although not statistically significant, but had no association with diarrhoea (RR: 1.00, 95% CI: 0.68–1.45) or viral infections (RR: 1.12, 95% CI: 0.79–1.60). Models also suggested that the relationship between household toilets discharging to drains and enteric infection risk may vary by season. Conclusions: The presence of a household toilet was associated with lower risk of bacterial and protozoal enteric infections, but not diarrhoea or viral infections, suggesting the health effects of sanitation may be more accurately estimated using outcome measures that account for aetiologic agents.